The infection of ectoparasitic protozoa on farmed Nile tilapia (Oreochromis niloticus) at three reservoirs in Central Java, Indonesia - Waleed Kolia; SUNARTO SUNARTO; TETRI WIDIYANI (Society for Indonesian Biodiversity, 2021)
Abstract. Kolia WSK, Sunarto, Widiyani T. 2021. The infection of ectoparasitic protozoa on farmed Nile tilapia (Oreochromis niloticus) at three reservoirs in Central Java, Indonesia. Biodiversitas 22: 1975-1980. There is an expansion of fish culture in Indonesia, but there is a dearth of information on the parasitic infecting cultured fish. This study was conducted to investigate the occurrence of ectoparasitic protozoans on farmed Nile tilapia (Oreochromis niloticus) at three reservoirs (i.e., Cengklik, Mulur, and Gajah Mungkur) in Central Java, Indonesia, and to determine the prevalence, mean abundance, and mean intensity of such parasites. A total of 189 samples were collected from different cages. The sex of the fishes was determined and their lengths and weights were measured. The gills, fins, and skin were examined for ectoparasitic protozoa using a light microscope. Among the examined fishes, 146 samples were infected at the rate of 77.2 %. Mulur reservoir had the highest prevalence rate with 90.4%, followed by Cengklik and Gajah Mungkur with 82.5 % and, 58.7%, respectively. We found female fishes were more susceptible to the infection than males. Seven parasite species were identified, namely: Tetrahymena corlissi, Apiosoma spp., Trichodina spp., Cryptobia spp., Chilodonella spp., Ambiphrya spp., and Ichthyophthirius multifiliis. The protozoan parasite Trichodina spp. recorded the highest prevalence, mean intensity, and mean abundance among all the other protozoan species at the three reservoirs. The results provided a significant difference at (p<0.01) in the total number of parasites among the reservoirs. Despite the parasite infection, the physical and chemical parameters of the water of the three reservoirs were within the recommended range for the culture of Nile tilapia under the cage systems.